2014
DOI: 10.1152/ajpregu.00179.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain nucleus tractus solitarius glucagon-like peptide-1 receptor signaling reduces appetitive and motivational aspects of feeding

Abstract: Alhadeff AL, Grill HJ. Hindbrain nucleus tractus solitarius glucagon-like peptide-1 receptor signaling reduces appetitive and motivational aspects of feeding. Am J Physiol Regul Integr Comp Physiol 307: R465-R470, 2014. First published June 18, 2014 doi:10.1152/ajpregu.00179.2014.-Central glucagon-like peptide-1 receptor (GLP-1R) signaling reduces food intake by affecting a variety of neural processes, including those mediating satiation, motivation, and reward. While the literature suggests that separable n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 28 publications
2
67
1
Order By: Relevance
“…Pharmacological activation of was a change similar to that elicited by cholecystokinin (CCK) and leptin, endogenously expressed peptides shown to modulate the activity of GCG neurons (39,40). The action potential firing frequency in unlabeled neurons was not affected by CNO perfusion We then tested whether GCG neuronal activacentral GLP-1Rs has clearly been shown to lead to a reduction in food intake (7,15,17,20,26,(41)(42)(43)(44)(45). To examine whether central GCG neuron activation is sufficient to reduce feeding, we stimulated GCG neurons in fed and fasted animals and measured chow food and high-calorie diet (HCD) intake.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological activation of was a change similar to that elicited by cholecystokinin (CCK) and leptin, endogenously expressed peptides shown to modulate the activity of GCG neurons (39,40). The action potential firing frequency in unlabeled neurons was not affected by CNO perfusion We then tested whether GCG neuronal activacentral GLP-1Rs has clearly been shown to lead to a reduction in food intake (7,15,17,20,26,(41)(42)(43)(44)(45). To examine whether central GCG neuron activation is sufficient to reduce feeding, we stimulated GCG neurons in fed and fasted animals and measured chow food and high-calorie diet (HCD) intake.…”
Section: Resultsmentioning
confidence: 99%
“…The stimulatory effects of leptin on VTA function are mediated via LepRb neurons in the LHA, which innervate the VTA [75]. Finally, recent data demonstrated that the above mentioned homeo-static and anorexic aspects of feeding substantially interact with hedonic feeding paradigms [79,80], and complex behaviors like feeding should be understood as an integration of distinct feeding behaviors [81] (Fig. 3C).…”
Section: Leptin and Central Control Of Energy Homeostasismentioning
confidence: 99%
“…Recent evidence has shown that GLP-1R activation in nuclei like the NTS, historically a nucleus believed to solely regulate homeostatic or non-reward related feeding, can also suppress motivation to eat and the rewarding value of food (as measured by progressive ratio operant responding and conditioned place preference, respectively)[32,33]. The mechanisms for this reward-suppression are still unclear.…”
Section: Central Actions Of Glp-1 On Food and Drug Rewardsmentioning
confidence: 99%